Sistem Pengendalian Manajemen Terhadap Sistem Insentif Kepada Tenaga Pengajar Lokal Dan Asing Di Sekolah Cita Hati - Hwihanus Hwihanus; Grace Lodita Hatumena; Alifiarisma Maricar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to find out how the management control system at the Cita Hati Foundation is regarding the incentive system given to local teaching staff and foreign teaching staff. The data source for this research uses primary and secondary data. The aim of this research is to display, explain and analyze the function of implementing a management control system. This research uses a qualitative descriptive approach, which is usually used to describe and describe current phenomena, whether human engineering or natural. Primary data was obtained directly from the Cita Hati Christian School, which was the subject of the research. By conducting direct observations at the Cita Hati Christian School and interviews with people at the school who are related to this research. The results obtained are that the Cita Hati Foundation has teaching staff who are competent in their fields, not only local teaching staff, but also bringing in foreign teaching staff to improve the quality and value of education. The presence of foreign teaching staff has both positive and negative impacts on the foundation, especially local teaching staff. This is due to the differences in treatment given by the foundation to the two. So the researchers suggest that the Cita Hati Foundation evaluate and revise the incentive program that will be given to employees, in accordance with the policies that have been determined or agreed and the point is that the policies made must be in accordance with the Foundation's ability to provide incentives in accordance with employee performance. This will encourage better performance so that the company can also develop forward with employees who are loyal and willing to develop together.